Taxonomic revision of the Neotropical stalk-eyed fly Plagiocephalus Wiedemann (Diptera, Ulidiidae, Ulidiinae) - Vasconcelos,Ana Caroline O. (2019)
ABSTRACT Plagiocephalus is a genus composed of three species mainly recognized by the males with stalked-eyes. Plagiocephalus lobularis is distributed from Northeastern Brazil to North of Argentina, P. latifrons is distributed from Mexico to Bolivia, and P. intermedius occurs in Costa Rica. We review the species of the genus, providing new diagnostic characters, an identification key, and new information on the terminalia of Plagiocephalus. Also, we update the geographic distribution of the species of the genus.